Analisis Peran Puri Dalam Strategi Mobilisasi Sumber Daya Gerakan Trash Hero Di Kecamatan Blahbatuh Tahun 2019-2022 (Jurnal Nawala Politika, 2023)
The problem of plastic waste is an environmental problem caused by the lifestyle of people using single-use plastic products. The phenomenon of plastic waste in Blahbatuh District has sparked community initiatives by joining the Trash Hero Movement. The strategy of movement actors in mobilizing resources to develop the movement is examined qualitative-descriptive. Utilization of resources available in the environment effectively, can mobilize people to become members of the movement. Understandings related to social movements are analyzed using resource mobilization theory by McCarthy and Zald. The purpose of this research is to explain the role of Puri Ageng Blahbatuh towards the strategy of the Trash Hero Blahbatuh Movement in developing a global movement for local communities in Blahbatuh. The meeting of the traditional concept of Puri with the global concept of Trash Hero Movement is interesting to study. Keywords: Plastic Waste, Trash Hero Movement, Resource Mobilization, Puri